The effect of the thickness of steel pipe in linear and 2-dimensional stiffness analysis during design of transmission tower. Issue 1 (January 2021) - Song, Yuxi; Chen, Xianqi; Di, Zijian; Sun, Yihang
Abstract: Transmission towers are truss structures which are used to support the transmission power lines. It is important to design the transmission towers because unsuitable dimensions could waste the steel or lead to the failure of transmission towers. The thickness of the beam is a critical parameter during the design of transmission tower, which is directly related with the safety of the transmission tower. In this paper, a finite element method in linear and 2-dimension was employed to simulate the mechanical behaviour of transmission tower. Based on the calculated results, the variations of the maximum stress and the maximum displacement with the increasing thickness were displayed. Both the stress and displacement decrease dramatically with the increasing thickness and reach to a stable value if the thickness is beyond a critical thickness. When the thickness changes from 1 mm to 4 mm, the maximum stress and the maximum displacement decrease by 74%. When the thickness is more than 4 mm, the reduction of stress and displacement is not obvious. The percentage reduction of more than 70% is determined to be the criterion for optimum thickness. The relationships can be used in the design of the transmission tower.